Pengaruh Tingkat Kinerja dan Manajemen Laba terhadapManajemen Kesan: Studi Empiris pada Perusahaan Manufaktur Subsektor Makanan dan Minuman yang Terdaftar di BEI Tahun 2017-2020 - Nabila Amanda; Halmawati Halmawati (Universitas Negeri Padang, 2022)
This study aims to determine the effect of financial performance and earnings management on impression management in the MD&A section of the annual report. The type of research used is associative-quantitative with multiple linear regression analysis. The population in this study are all manufacturing companies in the food and beverage sub-sector listed on the Indonesian’s Stock Exchange in 2017-2020. Sampling in this study used purposive sampling method and resulted in 84 research samples. impression management variables were analyzed through content analysis to measure the intensity of impression management. Financial performance variable is measured using return on assets (ROA). Earnings management variable is measured using discretionary accruals with modified Jones model. The results of this study prove that financial performance and earnings management have a negative effect on impression management in the MD&A section of the Annual Report.